Advancing Ocean Governance in Marine Regions Through Stakeholder Dialogue Processes - Weiand, Laura; Unger, Sebastian; Rochette, Julien; Müller, Alexander; Neumann, Barbara (Frontiers in Marine Science, 2021)
The poor state of the ocean and the transboundary nature of the marine environment require bold action by States coordinated across sectors and territorial boundaries in order to deal with the manifold challenges the ocean is facing—and with it humankind. Cooperation and coordination among States and stakeholders in marine regions have proven to be important levers for policy implementation and to strengthen ocean governance, yet remain challenging. Transparent and engaging stakeholder dialogue processes have the potential to provide guidance for the necessary transformation toward ocean sustainability and support the attainment of Sustainable Development Goal (SDG) for the ocean, SDG 14 and other interlinked ocean-related targets. The aim of this study is to review the challenges and opportunities of current collaborative efforts, namely multi-stakeholder dialogue and exchange processes, within and between marine regions to accelerate transformative action, contributing to these global goals. This paper builds on knowledge co-production and collaborative governance literature, and reviews experiences by stakeholders with ocean-related science-policy interfaces in an effort to strengthen regional ocean governance. As an exemplary case of such interfaces, this study assesses the Marine Regions Forum, a newly established inclusive dialogue and exchange platform for diverse actors from marine regions that aims to provide an informal space for joint learning and support regional action and international governance processes alike. Employing latent content analysis of interviews with experts, critical common barriers that hamper current collaborative efforts amongst stakeholders in marine regions are identified, such as fragmented governance frameworks, power and resource imbalances, and lack of meaningful stakeholder engagement. Pathways to address these challenges, such as through common goal orientation, contextualisation, inclusivity, trust building and meaningful continuous interactions are also identified. This paper concludes by discussing the value added of transparent and inclusive collaborative processes in the transformation of ocean governance toward achieving sustainability.